Association of PC Use and TV Viewing Hours with Women’s Recreational Physical Activity and Its Impact on Their Obesity Indices - John Spanoudaki, Maria; Theodoros Cheimaras, Antonios; Pavlos Papadopoulou, Maria; Dimitrios Rountos, Prokopios (Arab Journal of Nutrition and Exercise (AJNE), 2022)
Background: Television (TV) viewing and computer (PC) use have been associated with poor health outcomes. Aim: To investigate the association of TV viewing and PC use with recreational physical activity energy expenditure (RPAEE), obesity indices, physical activity levels (PAL) and body fat percentage (BF%) of adult women. Methods: Bodyweight (BW), height, waist (WC) and hip (HC) circumferences of 150 adult women were measured. Body mass index (BMI) and waist-to-hip ratio (WHR) were calculated. The BF% was measured by bioelectrical impedance analysis. The Athens Physical Activity Questionnaire was used to assess PAL, RPAE, TV viewing and PC hours. Results: The majority of women (53%) were overweight and obese, watched TV for >14 hr/wk (59%), and almost half (47%) of them used computers for >1 hr/day. Slightly more than half of them (54%) had a sedentary lifestyle and reported exercise participation for <2 hr/wk. No walking for leisure was reported by one-third of the subjects, while an alarming low percentage (0.7%) walked only 2.5 hr/wk. No participation in informal physical activity was reported by 69%. RPAEE was estimated at 982 ± 973 kcal/wk and negatively correlated to TV-watching hours (r = –0.31, p < 0.05), computer use (r = –0.3, p < 0.05), BMI (r = –0.44, p < 0.01), BW (r = –0.44, p < 0.01), WC (r = –0.41, p < 0.01), WHR (r = –0.31, p = 0.01). Moreover, RPAEE and BF% were negatively correlated (r = –0.44, p < 0.01). BF% was associated with long hours of PC use and TV watching (R2 = 0.11, F1.148 = 17.94, p = 0.00; R2 = 0.14, F1.148 = 5.4, p = 0.002). Conclusion: Screen use affecting obesity indices seemed to overrun recreational time for physical activity participation and dominate women’s lifestyle. Further research targeting behavioral change practices is recommended. Keywords: obesity, women, physical activity, recreational physical activity expenditure